Tinjauan Terhadap Keringanan Penjatuhan Pidana Sebagai Insetif Dalam Tindak Pembunuhan Berencana Kepada Justice Collaborators - Kartolo, Rahmat; Fitriasih, Surastini (Faculty of Law, Andalas University, 2024)
This article aims to examine the reduction of criminal penalties as a form of reward or incentive for justice collaborators. This is prompted by the pro and con debate over the verdict of the Panel of Judges in the case of Barada Richard Eliezer, who was sentenced to 1 year and 6 months for the planned murder of Brigadir Nofriansyah Yosua Hutabarat. The legal issue revolves around the absence of clear criteria for the extent of such leniency, as it remains within the prerogative of the judge. This research is conducted using normative legal research, involving an analysis of all relevant laws and regulations related to the legal issue under investigation. These include the Supreme Court Circular Letter Number 4 of 2011 on the treatment of crime reporters (whistleblowers) and justice collaborators in specific criminal cases, and the Republic of Indonesia Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 on Witness and Victim Protection. The research results suggest the need for consistency in judicial decisions regarding the extent of sentence reduction for justice collaborators. The author recommends considering the Italian regulations in dealing with organized crime, where defendants who are willing to become justice collaborators, thereby assisting in uncovering criminal groups and providing necessary evidence, may receive reduced prison sentences. A life sentence can be replaced with a prison term of 12 to 20 years, and other sentences can be reduced by one-third to two-thirds. According to the author, this reduction can be determined based on the maximum criminal penalty they face, as stipulated in Article 199 of the Draft Criminal Procedure Code (RUU KUHAP).